Let's start with Jesus a new way of doing theology - Kinlaw, Dennis F. 1922- (Grand Rapids, MI Zondervan, 2005)
Includes bibliographical references and indexes.
Keywords: Theology, doctrinal; Jesus Christ -- person and offices